Optimalisasi Peran Guru Pendidikan Agama Islam dalam Mewujudkan Profil Pelajar Pancasila - Wati, Hani Fatma; Astutik, Anita Puji (PAI RAFAH, 2024)
Education in the 21st century faces severe challenges by the next generation who are experiencing a decline in the character of each personality and the fading of knowledge related to Pancasila values in the application of every daily life. The independent curriculum contains a breakthrough in strengthening character education by proclaiming, establishing, and realizing the Profile of Pancasila Students as a competency that needs to be instilled in students. The purpose of this study is to determine the optimizing of the role of Islamic religious education teachers along with the challenges and solutions in realizing the profile of Pancasila students. The method used is qualitative methods that have a descriptive nature with the stages of observation, interview, and documentation. This study found that the education teacher at SMP Negeri 1 Sidoarjo is optimal. By having several personal principles such as comprehensive principles, broad insight, and exemplary principles. The challenges are in the form of an exemplary application of other subjects teachers and parents with the solution of establishing cooperation for commitment in implementing and internalizing Islamic values against Pancasila